Unraveling mosaic viruses in contemporary agriculture: In-depth insights on characterization, impact, diagnosis, treatment, and management (2023)
Mosaic viruses are a constant concern for the agricultural sector. They pose a real threat to both food and ornamental crops, causing huge economic losses and even threatening food security in many regions. In this article, we will present a general overview of these viruses: their characteristics, transmission mechanisms, effects on crops and available control methods. We will see that one of the main difficulties in dealing with mosaic viruses is their diversity and wide host range. In addition, the lack of effective treatment alternatives and the practical challenges of diagnosing different mosaic virus species require constant epidemiological vigilance to prevent their spread. We will first present a general characterisation of mosaic viruses as an informal group of viruses belonging to tens of different taxa. We will then review the main symptoms of mosaic virus infection (hence the name "mosaic"), diagnostic methods, host range, transmission mechanisms and treatment options. Secondly, we will discuss the impact of these viruses on ornamental and food crops. Finally, we will look at some possible strategies for infection management and control.